Enterprising Minnesotans : 150 years of business pioneers - George, Stephen, 1948- (University of Minnesota Press, 2003)
In Enterprising Minnesotans we read stories of the men and women throughout Minnesotas history who have created exceptional businesses from 1849 to the present, including Cargill, the Mayo Clinic, Andersen Windows, Ecolab, Schwans, and Leeann Chin, Inc. Through fascinating stories, Enterprising Minnesotans honors the creativity, tenacity, and boldness that enabled these men and women to transform their dreams into success.